Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 2964873 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "HasCoordinate is true", "HasGeospatialIssue is false", "Country is Denmark" ] } The dataset includes 2964873 records from 95 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000963-150221044754056/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences